Allergic bronchopulmonary aspergillosis as an initial manifestation of cystic fibrosis: Diagnostic and therapeutic implications in the era of CFTR modulators - Georgia Mitropoulou, MD; Zisis Balmpouzis, MD; Aurelia Oberhansli-Wavre, MD; Michael Morris, PhD; Sylvain Blanchon, MD; Alain Sauty, MD; Angela Koutsokera, MD, PhD (Journal of Allergy and Clinical Immunology: Global)
Allergic bronchopulmonary aspergillosis (ABPA) results from complex hypersensitivity reactions to Aspergillus fumigatus, which often occur in patients with asthma, cystic fibrosis (CF), or CF transmembrane conductance regulator (CFTR)-related disorders. Genetic predisposition, particularly variants of the CFTR gene, probably plays a significant role in the development of ABPA. We present the case of a 20-year-old male with ABPA and bronchiectasis that was initially misdiagnosed as a result of normal sweat chloride values and negative first-level genetic testing results. Comprehensive CFTR gene sequencing revealed 2 pathogenic variants, R347H and D1152H, which together with the clinical phenotype and functional tests, supported the diagnosis of CF. Treatment with elexacaftor/tezacaftor/ivacaftor resulted in significant clinical and functional improvement, including a marked decrease in total IgE levels, suggesting a potential role for CFTR modulators in controlling ABPA. This case illustrates the evolving understanding of CF as a spectrum of disorders in which CFTR dysfunction may manifest subtly and variably, necessitating a high index of suspicion and a comprehensive diagnostic approach to ensure timely treatment in the era of highly effective CFTR modulators.